Vecuronium and fentanyl requirement in abdominal surgery under combined epidural-general anaesthesia and general anaesthesia alone - Hossain, M; Hoq, MF; Rahman, MS; Yeasmeen, S; Ahmed, A; Huda, MR; Rahman, MM (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):55-59 The abstract of this article is available on the PubMed website